2005
DOI: 10.1038/nmat1455
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic transport by synthetic molecular machines

Abstract: Nature uses molecular motors and machines in virtually every significant biological process, but demonstrating that simpler artificial structures operating through the same gross mechanisms can be interfaced with-and perform physical tasks in-the macroscopic world represents a significant hurdle for molecular nanotechnology. Here we describe a wholly synthetic molecular system that converts an external energy source (light) into biased brownian motion to transport a macroscopic cargo and do measurable work. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
442
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 700 publications
(452 citation statements)
references
References 47 publications
4
442
1
5
Order By: Relevance
“…As a comparison, the 13 C CP/MAS NMR spectrum of the Igepal CO-630 pseudorotaxane has been included in Figure 7, which reveals the formation of a supramolecular system analogous to those obtained for their counterparts of 5 and 40 oxyethylene groups. Figure 9 shows the 1 H NMR spectra of pure -CD and the pseudorotaxane samples in DMSO-d 6 . No significant shifts of the Igepal surfactants and -CD resonances have been observed for the pure and pseudorotaxane solutions, thus indicating a complete disruption of the supramolecular complexes by solvent solvation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a comparison, the 13 C CP/MAS NMR spectrum of the Igepal CO-630 pseudorotaxane has been included in Figure 7, which reveals the formation of a supramolecular system analogous to those obtained for their counterparts of 5 and 40 oxyethylene groups. Figure 9 shows the 1 H NMR spectra of pure -CD and the pseudorotaxane samples in DMSO-d 6 . No significant shifts of the Igepal surfactants and -CD resonances have been observed for the pure and pseudorotaxane solutions, thus indicating a complete disruption of the supramolecular complexes by solvent solvation.…”
Section: Resultsmentioning
confidence: 99%
“…Freshly deionized water from a Millipore Q-System, with conductivities lower than 15 µSc m -1 , was used in the preparation of the samples. All the 1 H NMR samples were prepared in dimehtyl sulfoxide-d 6 (DMSO-d 6 , Aldrich Chemical Co., 99.96% minimum deuterium).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Berná et al demonstrated transfer of a liquid droplet on photoresponsive molecular shuttles containing rotaxane. [54] A fluoroalkane unit was prepared in the molecule shuttle. This unit could appear and be concealed by photoisomerization between fumaramide and maleamide under light irradiation.…”
Section: Dongliang Tianmentioning
confidence: 99%
“…In the large majority of cases, the drop motion is induced by an interfacial energy gradient at a solid/liquid interface (wettability gradient) and/or at a free interface (Marangoni stress) 3. This has resulted in a plethora of studies to elucidate the fundamental mechanisms that convert such gradients into drop motion4 as well as to develop strategies to manipulate drops under the control of various external signals, such as thermal,5 electrical2, 6, 7 and optical8, 9, 10, 11, 12, 13 stimuli. Most of these approaches necessitate the implementation of rather complex components, such as electrodes or optical elements, or the development of systems that are intrinsically responsive to the desired stimulus, such as photo‐ or thermosensitive substrates 8, 9.…”
mentioning
confidence: 99%
“…This has resulted in a plethora of studies to elucidate the fundamental mechanisms that convert such gradients into drop motion4 as well as to develop strategies to manipulate drops under the control of various external signals, such as thermal,5 electrical2, 6, 7 and optical8, 9, 10, 11, 12, 13 stimuli. Most of these approaches necessitate the implementation of rather complex components, such as electrodes or optical elements, or the development of systems that are intrinsically responsive to the desired stimulus, such as photo‐ or thermosensitive substrates 8, 9. This has led to the emergence of a broad variety of powerful drop actuation strategies that work in a laboratory environment, that is, require specific equipment and well‐controlled conditions (for example, protection from ambient light or precise control of temperature and surface tension).…”
mentioning
confidence: 99%